Comparative assessment of three sources of crude cassava water extract as bio-herbicide (2013)
Two experiments were conducted at Owode- Ijako in Ogun State, Nigeria between September 2006 and April 2007 to investigate the efficacy of three sources of Crude Cassava Water Extract (CCWE) as post emergence herbicide on weeds of cowpea. The trials were arranged in randomized complete block design and replicated three times. The treatments were 25% and 50% of Bulk sample, MS6 and TMS extracts respectively, and two controls; unweeded and handweeded in each trial. Herbicidal efficacies of CCWE in controlling cowpea weeds were evaluated using phytotoxicity, weed biomass and density. The results showed that spraying CCWE of Bulk and MS6 at 50% on cowpea weed caused 40 and 50% phytotoxicity respectively. There was no significant difference in weed biomass (65.3% and 74.5%) and weed density (79.92 and 80.33) of CCWE of bulk sample and MS6 respectively. Whereas handweeded achieved 98.68% and 96.65% weed biomass and density respectively. The growth attributes such as plant height, number of leaves and leaf area differed significantly due to different treatments. Grain yield and yield components of cowpea were significantly influenced by the application of CCWE from the three sources. Highest grain yield (540kg/ha) was recorded in handweeded plots but was comparable to plots sprayed with 50% CCWE of bulk samples (450kg/ha) and MS6 (430kg/ha) while least grain yield was recorded in unweeded plots.